2015
DOI: 10.1002/eji.201444979
|View full text |Cite
|
Sign up to set email alerts
|

The RNA‐binding protein HuR/ELAVL1 regulates IFN‐β mRNA abundance and the type I IFN response

Abstract: Secretion of type I interferon (IFN) isAdditional supporting information may be found in the online version of this article at the publisher's web-site

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 64 publications
0
42
1
Order By: Relevance
“…The IFN-β 3′ UTR contains a highly conserved ARE (63, 64), which has been shown to promote deadenylation of the IFN-β mRNA (63). Although TTP has not yet been directly implicated in regulating IFN-β expression, the ARE contains a perfect match to the consensus TTP binding site, UAUUUAU, and two additional, closely related sequences (62). Recent studies have used cross-linking and immunoprecipitation to identify transcriptome-wide targets of TTP (74, 75).…”
Section: Discussionmentioning
confidence: 99%
“…The IFN-β 3′ UTR contains a highly conserved ARE (63, 64), which has been shown to promote deadenylation of the IFN-β mRNA (63). Although TTP has not yet been directly implicated in regulating IFN-β expression, the ARE contains a perfect match to the consensus TTP binding site, UAUUUAU, and two additional, closely related sequences (62). Recent studies have used cross-linking and immunoprecipitation to identify transcriptome-wide targets of TTP (74, 75).…”
Section: Discussionmentioning
confidence: 99%
“…IL-6 mRNA is stabilized and degraded by AT-rich interactive domain-containing protein 5A and Regnase-1, respectively [40, 41]. IFN-β mRNA is stabilized by HuR protein, which binds to A/U-rich elements on 3′ untranslated regions [18, 42]. Prokunia-Olsson et al reported that IFN-λ mRNA was still detectable 24 h after poly I:C stimulation [43].…”
Section: Discussionmentioning
confidence: 99%
“…ELAVL1 (also known as HUR) is a RBP known to bind to AU-rich elements (AREs) (Herdy et al 2015). An interesting aspect of ELAVL1 is that it preferentially binds mRNAs that lack N 6 -methyladenosine (m 6 A) sites, stabilizing targeted mRNAs .…”
Section: Identification Of Previously Unrecognized Ribosomal Rbpsmentioning
confidence: 99%